Rationale for the use of quail meat in the production of food products for special purposes - A. M. Patieva; Z. N. Khatko; S. V. Patieva; A. V. Zykova (Новые технологии)
As a result of scientific research carried out on the materials and technical base of KubSAU named after. I.T. Trubilin and MSTU technological parameters and biological value of quail meat has been studied. Texas broiler quails, which were raised on a farm in the Krasnodar Territory, were slaughtered. The rationale for the use of Texas broiler quail meat in the technology of special-purpose meat products has been given. Studies of technological properties showed that the slaughter yield of an uneviscerated carcass is on average 85%. The yield of boneless meat was assessed in two ways: after gutting and after blanching the carcass, which showed that the yield of boneless meat after blanching was higher by 16.87 g, which was explained by a more thorough separation of muscle tissue from the bones. The results provided the basis for the use of blanching of whole carcasses in the production technology of special products based on quail meat. The recipe composition of meat cream based on quail meat and offal was modeled. Experimental batches were developed, followed by a tasting assessment and calculation of nutritional value, which showed high results, which justified the use of Texas broiler quail meat for the production of products for both general and special purposes.